Effects of two novel denture cleansers on multispecies microbial biofilms, stain removal and the denture surface: an in vitro study - Rattiporn Kaypetch; Pachara Rudrakanjana; Peerapong Tua-ngam; Orada Tosrisawatkasem; Sarut Thairat; Pairin Tonput; Pornpen Tantivitayakul (BMC, 2023)
Abstract Background The continuously increasing demand for removable denture appliances and the importance of adequate denture cleaning have led to the development of various denture cleansing products. The aim of this study was to evaluate the efficacy of two novel denture cleansing agents (GE and TM) and three commonly available cleansers (0.5% sodium hypochlorite; NaClO, 0.12% chlorhexidine gluconate; CHX, and Polident®; POL) on multispecies microbial biofilm formation, stain removal and physical properties of dentures. Methods The antimicrobial activities of denture cleansing agents were determined against major oral opportunistic pathogens including Streptococcus mutans, Staphylococcus aureus, Escherichia coli and Candida albicans, using time-kill assays. Multispecies microbial biofilms grown on acrylic resins for 72 h were generated to determine the antibiofilm effects of cleansing agents by confocal laser scanning microscopy (CLSM). Evaluations of the tea and coffee stain removal properties and the alterations in the physical properties of dentures were also performed. The toxicity of cleanser residues released from denture acrylics to fibroblast cells was investigated using MTT assay. Results All denture cleansing agents tested could effectively kill oral bacteria and Candida albicans. Furthermore, after immersion for more than 3 h, the cleansers Polident®, GE and TM could efficiently penetrate and inhibit multispecies denture biofilms with effects similar to 10 min of immersion in 0.5% NaClO. However, immersion in 0.12% CHX for 20 min showed less antibiofilm activity. The NaClO solution had the highest efficacy for removing stains from the artificial teeth. Conversely, the CHX solution enhanced tea and coffee staining, and the teeth immersed in this solution showed clinically unacceptable colour changes (ΔE > 5.5). However, the colour differences of teeth stained and immersed in POL, GE and TM cleansers were in the clinically acceptable range. There was no significant difference among the POL, GE and TM cleansers in terms of stain removal efficacy. The cleansers GE and TM did not alter the surface roughness and colour of the materials, moreover the residues of both cleansers did not exhibit cytotoxicity. Conclusion Two novel denture cleansing agents containing natural products, GE and TM exhibited effective antimicrobial activity, antibiofilm and stain removal capabilities without toxicity or disturbance of the physical properties of acrylics.